The Impact of Different Irrigation Protocols on the Bond Strength of Self-Adhesive Resin Cement to Radicular Dentin - Mihaela Vrebac; Dora Mohenski; Eva Klarić Sever; Bernard Janković; Lana Bergman; Ana Ivanišević (University of Zagreb. School of Dental Medicine, 2024)
Objective: The objective of the study was to investigate the influence of different irrigation protocols on the shear bond strength (SBS) of self-adhesive resin cement (SARC) on primed radicular dentin. Methods: Radicular dentin slabs (N=58) were embedded in acrylic. Subsequently, they were polished and randomly assigned to five experimental groups (N=8-12) and one control group, CG (N=8). Irrigation solutions used were 2.5% sodium hypochlorite (H), 17% ethylenediamine tetraacetic acid (EDTA), 9% etidronic acid with hypochlorite (HEDP), 0.9% saline solution (SS), and 2% chlorhexidine (CHX). Each experimental group underwent a different irrigation protocol for two minutes: 1) H/EDTA/H, 2) HEDP, 3) H/EDTA/CHX, 4) H/EDTA/SS and 5) HEDP/SS. The CG samples were not treated with any irrigation solution. After drying, the adhesive-enhancing primer (AEP) and dual-curing SARC were applied to the radicular dentin using molds corresponding to the Ultra Tester (Ultradent Products, South Jordan, USA). The specimens were stored at 37 °C in distilled water and broken after 10 days in shear mode. The results were analyzed using ANOVA and post-hoc Games-Howell test, α=0.05. Results: CG exhibited the highest SBS. With the exception of HEDP and HEDP/SS, all experimental groups showed significantly lower SBS compared to CG (p<0.05). Conclusions: HEDP appears to be an adequate solution for cleaning the root canal prior to dentin priming and fiber post cementation with SARC.